2003
DOI: 10.1034/j.1600-0676.2003.00817.x
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of integrity and function of isolated hepatocytes during extended suspension culture at 25°C

Abstract: Isolated hepatocytes in suspension provide a number of advantages for use in bioartificial liver device, however, poor stability of this cell preparation at physiological temperatures is an apparent barrier preventing their use. We therefore investigated the integrity and differentiated function of isolated rat hepatocytes under conditions of mild hypothermia. Isolated hepatocytes were suspended in a bicarbonate buffered saline medium, supplemented with glucose and bovine serum albumin (BSA), and maintained fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…allows to complete the characterization of major drugmetabolizing P450 activities prior to hepatocyte transThe urea synthesis rates noted in the present study were similar to those reported in either human hepatocytes in plantation. The hepatocytes from livers 2 and 3 showed a high suspension or monolayer cultures (16,32,46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…allows to complete the characterization of major drugmetabolizing P450 activities prior to hepatocyte transThe urea synthesis rates noted in the present study were similar to those reported in either human hepatocytes in plantation. The hepatocytes from livers 2 and 3 showed a high suspension or monolayer cultures (16,32,46).…”
Section: Discussionmentioning
confidence: 99%
“…We have selected this basic hepatic functions, such as synthesis of plasmatic proteins, urea synthesis or ammonia removal, and drug-metabliver function to assess the quality of hepatocyte suspensions. Urea formation from exogenous ammonia was olizing capacity, have been assessed for this purpose (2,13,32,42,46). Previous studies on the biochemical quantified using a fluorescence-based method.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, different cells, including skin (Trent and Kirsner 1998;Bravo et al 2000), ovarian (Gosden et al 1994;Harp et al 1994;Gunasena et al 1997), haematopoietic (Högman 1999aGulliksson 2000), hepatic (Stefanovich et al 1995;Wigg et al 2003), corneal (Bourne 1991;Lakey et al 2002), and even entire organs (Southard and Belzer 1995;St Peter et al 2002) are routinely conserved for short periods of time using hypothermic storage. The main goal of hypothermic preservation is to avoid or minimize hypothermia-induced injury and the simplest way to achieve it for short-term storage is the formulation of a physiological solution, or common culture media that modulates physiological response to cold by different means but mainly maintaining homeostasis (Ackers 2006).…”
Section: Introductionmentioning
confidence: 98%
“…Mechanisms contributing to hepatocyte injury and loss of function during extended suspension culture are not well understood. We hypothesized that oxidative stress and apoptosis were important mechanisms of cell injury in this setting, on the basis of known effects of hypothermia on the inhibition of oxidative stress 7,8 and apoptosis, 9,10 and our prior studies showing extended survival of isolated hepatocyte suspensions under conditions of mild hypothermia of 25°C 11 . Furthermore, it is known that cell detachment from an extracellular matrix leads to apoptosis, also named anoikis, in hepatocytes and a number of other epithelial cell lines 12–14 …”
Section: Introductionmentioning
confidence: 99%
“…The aim of the present experiments was to develop a strategy to improve the quality and integrity of isolated hepatocytes at 30°C. Although we previously demonstrated that hypothermia of 25°C is an effective technique for extending the survival of isolated hepatocytes in suspension, 11 the metabolic function of cells maintained at 25°C is only 35% of cells maintained at 37°C, making this strategy unlikely to be clinically useful. Cells maintained at 30°C have 60% of the metabolic rates of cells at physiological temperatures, making this temperature a more appropriate balance between cell survival and clinically useful metabolic function.…”
Section: Introductionmentioning
confidence: 99%